A WISPR of the Venus Surface: Analysis of the Venus Nightside Thermal Emission at Optical Wavelengths - J. Lustig-Yaeger; N. R. Izenberg; M. S. Gilmore; L. C. Mayorga; E. M. May; A. Vourlidas; P. Hess; B. E. Wood; R. A. Howard; N. E. Raouafi; G. N. Arney (The Planetary Science Journal, 2023)
Parker Solar Probe (PSP) conducted several flybys of Venus while using Venus’ gravity for orbital adjustments to enable its daring passes of the Sun. During these flybys, PSP turned to image the nightside of Venus using the Wide-field Imager for Solar PRobe (WISPR) optical telescopes, which unexpectedly observed Venus’ surface through its thick and cloudy atmosphere in a theorized, but until-then unobserved near-visible spectral window below 0.8 μ m. We use observations taken during PSP’s fourth Venus gravity assist flyby to examine the origin of the Venus nightside flux and confirm the presence of this new atmospheric window through which to observe the surface geology of Venus. The WISPR images are well explained by emission from the hot Venus surface escaping through a new atmospheric window in the optical with an overlying emission component from the atmosphere at the limb that is consistent with O _2 nightglow. The surface thermal emission correlates strongly with surface elevation (via temperature) and emission angle. Tessera and plains units have distinct WISPR brightness values. Controlling for elevation, Ovda Regio tessera is brighter than Thetis Regio; likewise, the volcanic plains of Sogolon Planitia are brighter than the surrounding regional plains units. WISPR brightness at 0.8 μ m is predicted to be positively correlated to FeO content in minerals; thus, the brighter units may have a different starting composition, be less weathered, or have larger particle sizes.